Update on the United States Nuclear Strategy: from NPR 2018 to NPR 2022 - Adam Potočňák (Vojenské rozhledy, 2023)
The article follows the author's comparative analysis of American and Russian nuclear doctrines and armaments from the fall of 2021. It presents the current nuclear strategy of the United States of America based on a content analysis of three specific areas of the updated version of the Nuclear Posture Review. Applying interpretive analysis and a rich secondary sources apparatus, the author also reflects on his 2021-formulated assumptions and expectations about the further development of American nuclear strategy under President Joe Biden. The author analyzes the influence of the presidential administration's ideological and political ambitions together with the decisive geopolitical events of 2022 and concludes that mainly due to the second factor, the current shape of American nuclear strategy has not undergone any revolutionary changes and continues to maintain a long-standing continuity and consensus about its basic principles.